MANAJEMEN KESISWAAN MAN 4 JOMBANG DALAM MENUNJANG PRESTASI PESERTA DIDIK - Azhar Syadza Fatinatun Nabilah; Nur Widyatus Sa'adah; Mafatikhatul Udhma; Latifatul Alini (Al-Nizam: Indonesian Journal of Research and Community Service, 2024)
This study aims to analyze student management at Madrasah Aliyah Negeri 4 Jombang (MAN 4 Jombang) in supporting student achievement. The research focuses on strategies, programs, and challenges in student management. A qualitative research method was employed, using data collection techniques such as observation, in-depth interviews, and documentation. The results show that student management at MAN 4 Jombang encompasses structured planning, implementation, supervision, and evaluation of student activities. Flagship programs, including merit-based new student admissions, integrated academic and religious development, character building through the 5S habituation (smile, greet, salute, polite, courteous), counseling services, and extracurricular development, have proven effective in enhancing both academic and non-academic achievements. Collaboration between the school, parents, and external institutions further strengthens the implementation of student management. Regular evaluations and technology-based monitoring systems support transparency and accuracy in assessment. These findings are expected to serve as a reference for developing student management in other madrasahs to improve education quality and student achievement.